1997
DOI: 10.1007/s004360050250
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of prostaglandins in pathogenic and nonpathogenic strains of Acanthamoeba spp.

Abstract: The aim of the present study was to examine the biosynthesis of prostaglandins and to investigate factors conditioning their biosynthesis in pathogenic and nonpathogenic strains of Acanthamoeba spp. We established that the activity of the synthase of prostaglandins was almost identical in pathogenic and non-pathogenic strains and that the synthesis of endoperoxide prostaglandins was similar to that of other organisms up to the point at which prostaglandin H2 was produced. The course of biosynthesis in vitro ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
7

Year Published

2000
2000
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 10 publications
(11 reference statements)
0
36
0
7
Order By: Relevance
“…The Acanthamoeba trophozoites secrete a variety of proteases with nonspecific collagenolytic activity to facilitate the invasion and degradation of stroma. These include serine proteases, cysteine proteases, metalloproteinases, elastase, collagenolytic enzyme, phospholipase A and a novel plasminogen activator [24,27,58]. Studies have shown the direct role of extracellular proteases in Acanthamoeba keratitis by co-incubating corneal epithelial cells with Acanthamoeba conditioned medium, which resulted in host cell cytotoxicity [65].…”
Section: Stromal Invasionmentioning
confidence: 99%
“…The Acanthamoeba trophozoites secrete a variety of proteases with nonspecific collagenolytic activity to facilitate the invasion and degradation of stroma. These include serine proteases, cysteine proteases, metalloproteinases, elastase, collagenolytic enzyme, phospholipase A and a novel plasminogen activator [24,27,58]. Studies have shown the direct role of extracellular proteases in Acanthamoeba keratitis by co-incubating corneal epithelial cells with Acanthamoeba conditioned medium, which resulted in host cell cytotoxicity [65].…”
Section: Stromal Invasionmentioning
confidence: 99%
“…Amebic proteolytic enzymes include serine proteases (11,28,29), contact-dependent metalloproteases (17), elastases (9), cysteine proteases (11), and cytotoxic proteinases, induced by mannose-mediated adhesion (21). The use of gelatin gels has shown the presence of several proteolytic enzymes secreted by the amebae in medium conditioned by cultured amebae (1).…”
Section: Discussionmentioning
confidence: 99%
“…Both pathogenic and nonpathogenic Acanthamoeba species endogenously produce a variety of prostaglandins, including PGE 2 , PGD 2 , and PGF 2␣ (48). However, pathogenic species produce more PGF 2␣ than nonpathogenic species.…”
Section: Protozoal Infectionsmentioning
confidence: 99%